PAKET TEKNOLOGI BAWANG MERAH DI LUAR MUSIM TANAM DI PANDEGLANG BANTEN - Resmayeti Purba; Yati Astuti (Universitas Muhammadiyah Purwokerto, 2013)
This study aimed to identy profits technology package for off season period in Pandeglang, Banten Province on March to May 2013. In this study four technology package, suitable for off season condition were tested, that was package technology A (Katumi varieties), technology B (Bima Brebes varieties), techonology C (Manjung varieties) and technology D (local varieties). Based on the t test analyses known that applications of package technology on data ofshallot production was analyzed and compared amongthe technology packages and farmers. To determine the financial feasibility of shallot cultivationin off-season period use ratioB/C was analyzed, while for measuring the level of package technological excellence applied to farmers to use marginal benefit cost analysis (MBCR). The study showed that the application of package technology C that was varieties Manjung, higher than package techonology A with varieties Katumi, technology B with varieties Bima Brebes, and local variety of ways farmers were 12.65 t/ha, 7.84 t/ha, 4.50 t/ha and 3.37 t/ha respectively. Introduction of package technology C with Manjung varieties can benefit shallot cultivation in the off season period is bigger than the technology D way farmers with local varieties. The profit shallot farming was of package technology A of Rp. 49.592.000/ha with value of ratio B/C 1.00, technology B of Rp. 123.072.00/ha with value of ratio B/C 2.49, package technology C of Rp. 232.717.000/ha with value ratio B/C at 4:48 and technology D, the way farmers are of Rp. 30.150.000/ha with value ratio B/Cat 0.68, respectively. Results of this study can be used as an alternative to shallot cultivation off season period using package techology C because of value of MBCR. 39.63. Keywords: shallot, package technology, off season